Analysis Of The Early Warning System Model As Supporting The Performance Of Sharia Insurance Companies At PT. Takaful Insurance - Iis Herike; Muhammad Ramadhan; Nurul Jannah (Jurnal Price : Ekonomi dan Akuntasi, 2024)
This research aims to determine the early warning system which consists of the ratio of changes in surplus, the ratio of management costs, the ratio of premium receivables to surplus in sharia life insurance companies in Indonesia during the 2015 period. PT. Takaful insurance does not reach the Solvency Level Limit (RBC) value set by the government. An early warning system is a tool that can be used by companies to anticipate a decline in the company's financial performance as well as a tool to assess the health of insurance companies. This type of research is quantitative with a descriptive approach, with quantitative / statistical data collection with the aim of testing the hypothesis that has been applied. If it is assumed that all early warning system factors as reflected in the aggregate surplus ratio, management fee ratio, and premium income to surplus ratio are fixed or constant, then the solvency level of the sharia insurance company has a constant value of 127.49, this means the minimum level of Solvency in sharia insurance companies, especially PT Takaful Indonesia, is 127.49% of the minimum regulatory limit for solvency levels which has been maintained at 120% (SK 481/KMK.017/1999). The resulting calculated t value for the surplus change ratio variable is 0.409 with a sig of 0.686. Sig analysis results. 0.686 is greater than 0.05, meaning that individually the ratio variable changes in surplus is significant to the level of solvency. The resulting calculated t value for the management expense ratio variable is -0.272 with a sig of -0.788. Sig analysis results. -0.788 is smaller than 0.05, meaning that individually the management fee ratio variable does not have a significant effect on the solvency level ratio. The resulting calculated t value for the premium receivables to surplus ratio variable is 2.807 with a sig of 0.010. Sig analysis results. 0.010 is greater than 0.05, meaning that individually the variable ratio of premium receivables to surplus does not have a significant effect on the solvency level ratio. The R square value is 0.173, which means that only 17% of the overall early warning system variable has no significant effect on solvency.